1990
DOI: 10.1071/ea9900599
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen rate and stocking rate effects on steer gains from grazed irrigated pangola grass in the Ord Valley, Western Australia

Abstract: Annual liveweight gain of steers grazing flood-irrigated, fertilised pangola grass in the Ord Valley, Western Australia, was modelled as a function of nitrogen rate (90-350 kg/ha) and stocking rate (5.2-12.6 steers/ha). Steer gains decreased linearly with increasing stocking rate (SR) at each nitrogen rate (NR). Increasing NR resulted in higher steer gains, particularly at the low levels of SR. The model predicted an increase in the slope (b values) of the linear relations between steer gains and SR with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A range in N fertilizer use efficiency of 1.3 to 4.7 kg steer gain per kg N applied was found for irrigated tropical pastures in Western Australia (Jones 1990). …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A range in N fertilizer use efficiency of 1.3 to 4.7 kg steer gain per kg N applied was found for irrigated tropical pastures in Western Australia (Jones 1990). …”
Section: Resultsmentioning
confidence: 96%
“…This N fertilizer use efficiency in steer gain is similar to that summarized for warm-season grasses fertilized at 110 kg N ha-' yr-' in the southeastern USA (Wilkinson and Langdale 1974), and for introduced cool-season grasses fertilized at 45 to 50 kg N ha-' yr-' in western North Dakota Lorenz 1969, 1974). As N application rates increased N fertilizer use efficiency in beef gain decreased in southeastern USA (Wilkinson and Langdale 1974), North Dakota (Rogler and Lorenz 1969), and Australian studies (Jones 1990). …”
Section: The Estimated 2 Million Ha Of Old World Bluestem Established Inmentioning
confidence: 95%
“…The efficiency of the animal gain which results from the efficiency of the herbage production and intake was estimated between 1.3 and 4.7 (Mears & Humphreys, 1974;Jones, 1990;Humphreys, 1991) and 1.8 kg liveweight per kg N (Euclides et al, 2007b). Fagundes et al (2005) similarly reported (Figure 2) that the efficiency of the higher N levels was reduced in swards of signalgrass (Brachiaria decumbens Stapf.…”
Section: Resultsmentioning
confidence: 99%
“…Fertilization Application of nitrogen (N) fertilizer has been widely used to increase animal production from pasture. Increases in annual LW gain have ranged from 1.3 to 4.7 kg LW/kg N (Jones, 1990;Humphreys, 1991). The gain in livestock production appears to be primarily due to the increased amount of forage produced.…”
Section: Strategies For Management Of Grasslandsmentioning
confidence: 99%